Moving the goalposts : a history of sport and society since 1945 - Polley, Martin, 1965- (Routledge, 1998)
This book argues that sport is not neutral, asocial or apolitical and so it needs to be assessed in its widest cultural context to be understood. It examines how sport is acted upon by these influences and creates influences of its own. The book provides a comprehensive survey of sport in Britain since 1945 and examines its place in British culture. It offers a critical introduction to existing literature on the subject and places contemporary sport in the context of recent history. The author discusses issues of politics, national identity, gender, class and race and explores representations of sport in the media. Sports covered include: football, rugby, tennis and polo.